The re-introduction of captive bred cheetah into a wild environment, Makulu Makete Wildlife Reserve, Limpopo province, South Africa - Van Hoven, Wouter (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.